2018
DOI: 10.18632/oncotarget.24906
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter 1 expression as a marker of prognosis in oesophageal adenocarcinoma

Abstract: BackgroundThe current TNM staging system for oesophageal adenocarcinoma (OAC) has limited ability to stratify patients and inform clinical management following neo-adjuvant chemotherapy and surgery.ResultsFunctional genomic analysis of the gene expression data using Gene Set Enrichment Analysis (GSEA) identified GLUT1 as putative prognostic marker in OAC.In the discovery cohort GLUT1 positivity was observed in 114 patients (80.9%) and was associated with poor overall survival (HR 2.08, 95% CI 1.1-3.94; p=0.024… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Clinical data and information on study outcomes up until 31 December 2014 was retrieved via patient note review at the Northern Ireland Cancer Centre, as previously described [17]. Patient information included age at diagnosis, date of diagnosis, date of surgery, and patient sex.…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data and information on study outcomes up until 31 December 2014 was retrieved via patient note review at the Northern Ireland Cancer Centre, as previously described [17]. Patient information included age at diagnosis, date of diagnosis, date of surgery, and patient sex.…”
Section: Clinical Datamentioning
confidence: 99%
“…The primary aim of this study is to investigate the potential association between cigarette smoking, alcohol consumption, and esophageal adenocarcinoma survival. A secondary aim was to investigate the impact of these lifestyle factors on survival, according to the expression of the selected biomarkers, P53, HER2, GLUT1, and CD8 which have been shown to be associated with prognosis in esophageal adenocarcinoma [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, elevated GLUT1 expression has been observed in many epithelial malignancies, and high GLUT1 levels have been reported to be a prognostic marker for esophageal cancer. 6 Analysis of datasets from The Cancer Genome Atlas confirmed that patients with head and neck squamous cell carcinoma with a favorable immune and metabolic gene signature (high CD8A, high COX5B and low GLUT1) had better short-term and long-term survival compared with patients with an unfavorable signature. 7 Positive GLUT1 expression has also been associated with tumor regression grade and may be a useful predictive marker for response to chemoradiotherapy in rectal cancer.…”
Section: Introductionmentioning
confidence: 90%
“…GLUT1 expression is normally restricted to erythrocytes, endothelial cells at the blood–brain barrier and the placenta, and it is generally absent from normal epithelial cells. However, elevated GLUT1 expression has been observed in many epithelial malignancies, and high GLUT1 levels have been reported to be a prognostic marker for esophageal cancer . Analysis of datasets from The Cancer Genome Atlas confirmed that patients with head and neck squamous cell carcinoma with a favorable immune and metabolic gene signature (high CD8A, high COX5B and low GLUT1) had better short‐term and long‐term survival compared with patients with an unfavorable signature .…”
Section: Introductionmentioning
confidence: 96%
“…A detailed description of TMA construction methods within the Northern Ireland Biobank is given elsewhere. 21,22…”
Section: T I S S U E M I C R O a R R A Y ( T M A ) C O N S T R U C T mentioning
confidence: 99%